1998
DOI: 10.1177/014107689809101006
|View full text |Cite
|
Sign up to set email alerts
|

The one-stop dyspepsia clinic—an alternative to open-access endoscopy for patients with dyspepsia

Abstract: The most sensitive investigative tool for the upper gastrointestinal tract is endoscopy, and many gastroenterologists offer an open-access endoscopy service to general practitioners. However, for patients with dyspepsia, endoscopy is not always the most appropriate initial investigation, and the one-stop dyspepsia clinic allows for different approaches. We have audited, over one year, the management and outcomes of patients attending a one-stop dyspepsia clinic. All patients seen in the clinic were included, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…In conclusion, as for other symptoms such as dyspepsia and menorrhagia (Baskett et al 1996;Rutter et al 1998), the investigation of infertility could be rationalised to a One Stop approach (Gordts et al 2002). Pre-visit blood and semen testing combined with pelvic ultrasound, hysteroscopy and culdoscopy in the outpatient clinic provides a thorough assessment of infertile couples.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, as for other symptoms such as dyspepsia and menorrhagia (Baskett et al 1996;Rutter et al 1998), the investigation of infertility could be rationalised to a One Stop approach (Gordts et al 2002). Pre-visit blood and semen testing combined with pelvic ultrasound, hysteroscopy and culdoscopy in the outpatient clinic provides a thorough assessment of infertile couples.…”
Section: Discussionmentioning
confidence: 99%
“…there were no clinics that accepted referrals where there was a general suspicion of cancer. The indications for referral included: seven studies on post-menopausal or abnormal vaginal bleeding (20)(21)(22)(23)(24)(25)(26), six studies on breast symptoms (14,15,(27)(28)(29)(30), three for lower gastrointestinal (GI) symptoms (16,31,32), three for elevated prostate specific antigen (PSA) (17,18,33), three for testicular symptoms (34)(35)(36), two for urological symptoms (37,38), two for dyspepsia (39,40), one for haematuria (19), one for unexplained lymphadenopathy (41), and one for neck lumps (6). When reported, one-stop clinics were held in a hospital setting.…”
Section: Resultsmentioning
confidence: 99%
“…In another study, 88% of GPs said they were satisfied and would use the one-stop lymph node clinic again (41). In the third study, 91% of GPs rated the clinic as 'good' or 'very good', and 84% said they preferred the one-stop clinic for the management of patients with dyspepsia while only 11% said they preferred direct access endoscopy (40). Finally, one study reported that when patients were reassured by all tests being negative in the usual care multi-stop clinic, they were significantly more likely to have further clinic attendance than those reassured in the one-stop clinic (54.4% versus 44.4%, P = 0.0005) (15).…”
Section: Acceptability Of One-stop Clinicsmentioning
confidence: 99%
“…For instance, the majority (94%) of patients referred on the 2-week wait cancer pathway do not have cancer 8 and 25% of patients with dyspepsia do not require gastroscopy. 9 Therefore, open access endoscopy alone may not be adequate while referral to the out-patient clinic is also not ideal, because those patients will likely need a second visit for SOGD (or utilise the over-stretched endoscopy facilities in case of one stop dyspepsia clinics). One solution could be to 'realign' the clinical assessment with the endoscopic test in one visit.…”
mentioning
confidence: 99%